THE EFFECT OF ANEMIA TO CARDIOVASCULAR RISK, LIPID PROFILE, AND GLUCOSE MONITORING IN PATIENT WITH TYPE 2 DIABETES MELLITUS IN SANGLAH GENERAL HOSPITAl - F. N. Anggreini; G. P. Supadmanaba; R. Saraswati (Faculty of Medicine, Udayana University, 2017)
Type 2 Diabetes Mellitus (T2DM) is chronic progressive disease which mainly marked by impairment of glucose utilization. Diabetic patients have high risk of anemia which is mainly caused by nephropathy with subsequent decreasing secretion of erythropoietin from renal medullar cells. A cross sectional analytic research was carried out to evaluate the prevalence of anemia among patients with T2DM and its correlation with CVD risk factors measured in medical record at Diabetes Centre of Sanglah General Hospital. The hemoglobin level, blood glucose concentration, HbA1c and lipid profile were collected and analyzed from 157 medical records as research sample which consist of 78 men and 79 women. The frequency of anemia is found to be quite high, reaching 39.7% from all samples (cut off value, Hb=10g/dl). Anemia significantly increased the risk of vascular complication by 8.143 times compare to non-anemic subjects with T2DM (p=0.004). From this research is known that anemia in T2DM may have significant impact on evaluation, treatment adjustment, mortality, and morbidity as well as precipitating CVD and accelerate progression of nephropati to ESRD which are major cause of mortality and morbidity in T2DM. Keywords: type 2 diabetes mellitus, anemia, hemoglobin, cardiovascular disease.